GALDAR: A genetically encoded galactose sensor for visualizing sugar metabolism in vivo. - Sakizli, U.; Takano, T.; Yoo, S.K. (PLoS Biology, 2024)
Sugar metabolism plays a pivotal role in sustaining life. Its dynamics within organisms is less understood compared to its intracellular metabolism. Galactose, a hexose stereoisomer of glucose, is a monosaccharide transported via the same transporters with glucose. Galactose feeds into glycolysis and regulates protein glycosylation. Defects in galactose metabolism are lethal for animals. Here, by transgenically implementing the yeast galactose sensing system into Drosophila, we developed a genetically encoded sensor, GALDAR, which detects galactose in vivo. Using this heterologous system, we revealed dynamics of galactose metabolism in various tissues. Notably, we discovered that intestinal stem cells do not uptake detectable levels of galactose or glucose. GALDAR elucidates the role for galactokinase in metabolism of galactose and a transition of galactose metabolism during the larval period. This work provides a new system that enables analyses of in vivo sugar metabolism.